Trend of Technologies 4.0 in Brazil - what does the demand about the Public Selection MCTI/FINEP/FNDCT Grant to Innovation 04/2020 tell us? - Fernandes, Andre; Barros, Marcos Antonio; Hamatsu, Newton (Revista Ciência Agronômica, 2021)
Industry 4.0 is characterized by the use of big data & analytics, autonomous robots, simulation tools, horizontal and vertical systems integration, IoT, cloud computing, additive manufacturing, augmented reality and cyber security, what was transposed to agribusiness as Agriculture 4.0 or Agro 4.0. The Brazilian government has been implementing initiatives to promote this segment, the most recent being the Public Selection Technologies 4.0, to support the themes Agro 4.0, Smart Cities, Industry 4.0 and Health 4.0. The objective of this study is to characterize and evaluate the demand for supporting innovation in Brazilian companies through this notice, with emphasis on Agro 4.0. The demand was analyzed addressing the number of projects and values in relation to the size of the companies, the occurrence of key/enabling technologies, distribution by State and Region, technological partnerships with STIs and the narrowing of the selection process. The terms highlighted in the tag cloud were qualitatively analyzed and categorized. The results indicate that the country is on the threshold of a new technological revolution in the field, with strong indications towards the wide adoption of technologies that characterize Industry 4.0 and Agro 4.0. The existence of a large contingent of well-evaluated projects in all thematic lines that will not be able to receive a grant points to the need to continue fostering innovation in segment 4.0.